SWOT and AHP Analysis of Strategy Selection in Optimizing Work Units : Study on Operational Disturbance Control Work Unit of PT Semen Tonasa - Yatman, Setiawan; Mahlia, Muis; Yunus, Amar M (Journal of Business Issues, 2023)
PT Semen Tonasa is one of the cement producers in Indonesia and is part of PT Semen Indonesia. Since 2015, cement sales have reversed due to supply being greater than demand. This condition requires cement producers to work hard to increase their sales or reduce costs in order to survive. One of the company's efficiency programs is to reduce equipment maintenance costs by increasing preventive maintenance to reduce corrective maintenance. The operational disturbance control work unit is tasked with controlling equipment operational disturbances and is corrective maintenance. To increase preventive maintenance, the maintenance strategy must change by optimizing the business process of the operational disturbance control work unit. From the results of the study that has been conducted using strong weakness opportunity threats (SWOT) and analitycal hierarchy process (AHP) analysis, it shows that the operational disturbance control work unit is in quadrant 1 with a value of X = 1.24 and Y = 0.94 which is aggressive in making several changes. This study aims to test and analyze decision making in optimizing the work unit.